Toxicological Evaluation of Acetylsalicylic Acid in Non-Target Organisms: Chronic Exposure on Mytilus galloprovincialis (Lamarck, 1819) - Pagano, M.; Savoca, S.; Impellitteri, F.; Albano, M.; Capillo, G.; Faggio, C. (Frontiers in Physiology, 2022)
Pharmaceuticals are now considered to be established contaminants and their presence in water poses a real risk not only to the marine ecosystem, as they may adversely affect non-target organisms that are exposed to them, but also indirectly to humans. This is especially true for the model organism considered in this work, Mytilus galloprovincialis (Lamarck, 1819), a suspensivore and bioaccumulating organism that enters the human food chain. Among the most commonly used over-the-counter medicines, anti-inflammatory drugs certainly feature prominently, with acetylsalicylic acid (ASA) at the top. In this work, M. galloprovincialis specimens were exposed to two concentrations of ASA (10 and 100 μg/L) for 10 and 20 days to evaluate possible alterations in the decrease in regulatory volume (RVD) in digestive gland cells and the cell viability of both these cells and haemocytes. In addition, the histopathologicalogical condition index of the gills and digestive gland were evaluated. The data obtained showed that chronic exposure to ASA did not alter the cell viability of haemocytes and digestive gland cells, but alters the physiological mechanisms of volume regulation in the digestive gland and, in addition, a time-dose reaction to ASA in the gills and digestive gland showing numerous alterations such as lipofuscin deposits and haemocyte infiltration was found. These results confirm the potential toxicity to the marine biota, highlighting the necessity to deepen the knowledge regarding the link between over-the-counter pharmaceuticals and non-target organisms.